FAKTOR PELAYANAN, PROMOSI DAN REPUTASI TERHADAP MINAT NASABAH MENGGUNAKAN PRODUK TABUNGAN HAJI PADA BRI SYARIAH KANTOR CABANG PEMBANTU MAGELANG TAHUN 2019 - Muhajir; Fathudin; Amat Ulya Inayah (Jurnal ini dipublikasikan oleh Pusat Penelitian dan Pengabdian Publikasi (P3M) STAI Nahdlatul Watan Samawa-licensed under a Creative Commons Attribution-ShareAlike 4.0 International License., 2021)
The research is aimed at seeing how promotion and reputation service affect customer’s interests using the haj saving product on loan to BRI Syariah Magelang Sub-Branch Magelang. The research uses a quantitative study method with data collection teachiques using a questionnaire. The sample in this research use probability sampling, namely 126 BRI Syariah Hajj Savings Customers in Magelang Sub-Branch Offices. The research method used is multiple linear regression analysis, classical assumption test, the coefficient of determination R. Hypothesis testing with simultaneous t test and F test. The results showed that partially and simultaneously service. The results showed that partially, service with t value of 4,360> t table 1,979, promotion with t count of 5,223> t table of 1,979 and reputation of t count of 7,064> t table of 1,979 with an effect on customer interest in using Hajj savings products at BRI Syariah. Magelang Sub Branch Office. And service, promotion and reputation simultaneously influence 32.1% of customers' interest in using Hajj savings at BRI Syariah Magelang Sub-Branch Office.